Caspofungin paradoxical growth in Candida albicans requires stress pathway activation and promotes unstable echinocandin resistance mediated by aneuploidy - Wei, Ying; Wang, Jing; Tang, Nan; Lin, Ziwei; Li, Wenhui; Xu, Yi; Guo, Liangsheng (Frontiers in Cellular and Infection Microbiology, 2025)
Paradoxical growth (PG) is a counterintuitive phenomenon in which otherwise susceptible fungal cells resume proliferation at supra-MIC concentrations of echinocandins, thereby undermining the efficacy of these frontline antifungals. Despite its clinical significance, the genetic basis of PG remains poorly understood. Here, we systematically dissect the roles of key stress response pathways—Hsp90, PKC, calcineurin, and TOR—in mediating caspofungin (CSP)-induced PG in Candida albicans and uncover a novel genetic mechanism involving segmental aneuploidy. Disruption of these pathways via pharmacological inhibition or targeted gene deletion abolished PG, confirming their essential roles in mediating adaptive stress responses. Whole-genome sequencing of CSP-tolerant isolates revealed a recurrent segmental monosomy on the right arm of Chromosome R (SegChrRx1). Phenotypic reversion analyses demonstrated that CSP resistance is reversible and directly linked to the presence of this aneuploidy. Transcriptomic profiling of SegChrRx1 strains showed broad transcriptional remodeling, including upregulation of GSC1 (encoding β-1,3-glucan synthase), CHS3 and CHS4 (chitin synthases), and key regulators of the PKC and calcineurin pathways, alongside downregulation of dosage-sensitive genes whose deletion enhances CSP resistance. Collectively, our findings reveal a dual mechanism of PG: activation of stress response pathways confers initial survival, while segmental aneuploidy enables reversible transcriptional reprogramming that promotes drug resistance. This study establishes segmental aneuploidy as a dynamic and previously underappreciated mechanism of echinocandin adaptation in C. albicans, with important implications for antifungal therapy.